Integration of Culture and Tourism Enabled by the Gaming Industry from the Perspective of Field Transformation: A Case Study of "Black Myth: Wukong" - Liu Mengyao; Wang Pengfei; Wang Chaoyue; Fan Lihui (Redai dili)
With the rapid growth of the digital economy, integrating the cultural and tourism industries has become a key driver of regional economic development and industrial upgrading. As a vital component of the cultural and digital sectors, the gaming industry facilitates integration through digital innovation and creative design. While existing research on cultural-tourism integration is extensive, little attention has been paid to how virtual cultural symbols transform and drive this process in the digital era. Recent advancements in gaming have blurred the boundaries between virtual and real experiences through virtual scene construction, cultural symbol reproduction, immersive interactions, and social media dissemination, accelerating the transformation of cultural resources into tourism assets. Understanding how the gaming industry promotes cultural-tourism integration enhances existing research frameworks, deepens insights into the dissemination and reproduction of cultural symbols in the digital economy, and offers new regional cultural tourism development strategies. Using Black Myth: Wukong as a case study, this research applies the field conversion theory to examine the flow and transformation of cultural symbols between virtual and real-world tourism contexts. It explores two key questions: (1) How does the gaming industry reconstruct traditional cultural symbols through digitalization and integrate them into real-world tourism using field conversion mechanisms? and (2) How does the participation and feedback of different groups influence the effectiveness of this integration, shaping the gaming industry's role in regional cultural tourism development? The findings indicate that digital technologies not only overcome spatial constraints on cultural resources but also enhance interactivity and dissemination, promoting the transformation of symbolic capital into cultural, social, and economic capital. However, engagement levels varied across groups. Players deeply immersed in virtual cultural symbols strengthened the connection between gaming and real-world tourism through social media, offline activities, and digital communities. In contrast, non-players rely on traditional tourism information sources and respond passively and indirectly to game-driven cultural symbols. This study identifies capital accumulation, habit migration, and stakeholder collaboration as the core mechanisms facilitating cultural-tourism integration. While gaming fosters cultural identity, tourism consumption, and economic diversification, it also presents challenges, such as infrastructure strain and tourism industry homogenization due to sudden visitor influxes. This research expands the scope of the theory's application by integrating the field conversion theory into the study of gaming and cultural-tourism integration. It examines how cultural symbols gain value through cross-field transformations. Furthermore, it highlights how digital games that leverage virtual reality, short videos, and social media facilitate cultural symbols' cross-regional flow and reproduction. Moving beyond static cultural transmission models, this study reveals the dynamic evolution of virtual culture and offers fresh perspectives on the development of the cultural industry in the digital economy.